Radioactive iodine therapy strategies for distinct types of differentiated thyroid cancer: a propensity score–matched analysis - Guo, Honghao; Zhang, Ning; Hu, Yixuan; Zhang, Furong; Huang, Tao; Shen, Na (Frontiers in Endocrinology, 2023)
Abstract Background: The management guidelines of radioactive Iodine (RAI) therapy for distinct types of differentiated thyroid carcinoma (DTC) were the same in clinical practice. However, in distinct types DTC, differences in RAI avidity and response existed and the effect of RAI therapy could not be equated. Methods: DTC patients’ data in SEER database were extracted to perform retrospective analysis. The differences between case group and control group were compared by chi-square tests. We used Kaplan-Meier statistics and Cox regression analyses to investigate cancer-specific survival (CSS). Propensity score–matched was performed to make 1:1 case-control matching. Results: 105195 patients who receiving total thyroidectomy were identified in SEER database. Compared to papillary thyroid carcinoma (PTC) (52.3%), follicular thyroid carcinoma (FTC) (63.8%) and oncocytic carcinoma of thyroid (OCA) (64.4%) had higher rates of RAI therapy. In the multivariable Cox regression model, RAI therapy was independent prognosis factor in PTC but not in OCA and FTC. In subgroup analysis, RAI therapy could improve prognosis in PTC when gross extrathyroidal extension or lymph node metastases or early survival when distant metastases (DM) were presented. However, OCA and FTC patients with DM rather than regional lesions only could benefit from RAI therapy. High-risk patients receiving RAI therapy showed a better prognosis in PTC but not in OCA and FTC. Conclusions: RAI therapy was an effective treatment for DTC and should be considered individually in PTC, OCA and FTC patients. Our results provided further guideline for treatment selection in DTC.